PENGOLAHAN TANDAN KOSOSNG SAWIT UNTUK KOMPOS DENGAN PENAMBAHAN LINDI - , Edhi Sarwono, Ir. Agus Prasetya, M.Eng,Sc.,Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Palm empty fruit bunches (PEFB) is solid waste which is highly available, but not very much utilized. That waste only sown in the field as mulch. The high accumulation of PEFB produces leachate that can pollute the environment. In general the purpose of this research is to observe the process of the PEFB composting with the principle of co â degradation of the PEFB and its leachate coming from the accumulation of PEFB. The research was done by feeding the leachate twice a day into a serie of reactors containing PEFB. Reactors are made of 4 inchi PVC with 130 cm height. Each reactor was feed with different concentration of leachate. The reactor were operated aerobically by flowing air at the flow rate of 75 L/h. The performance of composting process was monitored by observing the content of organic compound, organic carbon, nitrogen, ratio of C/N, cellulose, hemicelluloses, lignin of the PEFB, quality of leachate produced, reactor temperature, volume of liquid produced, decreasing of compost volume and mass, the water content and visual change within the reactor such as fungi,maggots and other organism. It was observed that fungi with the white collor of trunk and the bud,fungi with brown trunk and bud,and white decaying fungi,white small maggot,phoenix worm, fly,bitting midges,black ant and mites existed in all reactors. The presence of black soldier fly was only detected in the reactor feed with zero concentration of leachate (3rd reactor). Reduction of organic content, organic carbon, total lignocellulose of the PEFB added with leachate was more significant compare with that without leachate addition. However, reduction of C/N ratio was more important in the case of PEFB with no leachate addition. The highest decrease of BOD concentration of liquid product accured in the 3rd reactor (reactor with zero concentration of added leachate),ie 88%, whereas the highest decrease of COD concentration was observe in the 1st reactor (reactor with 100% concentration of leachate added), ie 89,7%. The 1st also showed the most significant decrease of compost volume. The concentration difference on leachate added, did not show significant difference on the result of both biodegradation of PEFB and leachate (liquid) generated.